Preliminary analysis of the questionnaire signals warning of relapse (AWARE) on peruvian drug addicts - Cristian Solano; Anthony Copez-Lonzoy (Interacciones)
The objective of the present study was to analyze the internal structure of the AWARE 3.0 questionnaire in drug addicts. A total of 240 subjects undergoing residential treatment (males n = 205 and females n = 35) between 18 and 61 years with the AWARE relapse alert scale were evaluated. The analyzes confirmed the existence of a single factor, in addition five confirmatory models were tested including the factor of method that demonstrated to influence in the original model. The reliability analysis obtained adequate scores for both observed and latent variables that represented equality at the conceptual and unit level (congeneric and tau-equivalent models). The results indicate a better fit only with the direct item model in addition to a short version. These findings provide a new perspective on the structure of the instrument and a new version that helps complement the evaluation in the process of evaluation and detection of relapse alert signals